Precising of Divisia Monetary Aggregates by Adding Differential Elasticity of Prices for Consumer Goods - Yevhenii ALIMPIIEV (Communications of International Proceedings, 2021)
At present, in the period of economic turmoil and price increases, there is a significant differentiation in both the pace and size of price changes for individual categories of goods and services. This phenomenon has a short- and medium-term effect and can be most easily quantified using the inflation elasticity of prices. Therefore, determining goods that have different inflation elasticity allows identifying the possibility for economic agents to use time arbitrage. This, may turn out to be a statistically significant factor determining the composition of the vector of financial assets in the extended consumption function. A hypothetical-deductive approach is used to demonstrate that during a period of general price increases, there is a significant variation in both the rate and magnitude of price changes for different categories of goods and services. These disparities have a direct impact on the preferences of economic agents, inter alia, on decisions related to the allocation of financial assets. In order to test the formulated deductive findings, the method of a simulation interview. The research shows that it is advisable to take into account the factor influencing the preferred choice of monetary assets and that is based on reasoning other than the expected yield. This factor can be taken into account in monetary statistics when calculating Divisia indices. Specifically, it is proposed to adjust the calculation method of Divisia indices by calculating weights of monetary aggregate components based on the differentiated elasticity of prices in response to the overall change in prices.
Keywords: Elasticity of Prices; Preferences of Economic Agents; Monetary Aggregates; Divisia Indices.